Some Indian Plant Gums - Their Botany, Chemistry and Utilization - Farooqi, M. I. H.; Kapoor, L. D. (Indian Forester, 1968)
About a dozen Indian plant gums of commercial as well as medicinal importance have been discussed. Some distinguishing chemical tests have been recorded which could serve to detect adulterations. Detailed chemical studies of the gum from Albi ia procera Benth. Have also been carried out as substitute for imported gum-arabic from Acacia senegal.